= 9n + 63
generate the first few terms using the recursive equation
f(1) = 72
f(2) = 72 + 9 = 81
f(3) = 81 + 9 = 90
f(4) = 90 + 9 = 99
the sequence is 72, 81, 90, 99, .....
This is an arithmetic sequence whose n th term formula is
=
+ (n - 1 )d
where
is the first term and d the common difference
d = 99 - 90 = 90 - 81 = 81 - 72 = 9 and
= 72
= 72 + 9(n - 1) = 72 + 9n - 9 = 9n + 63 ← explicit formula
Answer:
Which of the following questions allows for variability?
How many students visited the nurse on Monday, September 15, 2014, at your school?
How many free throws can a person make in one minute?
How much money do doctors earn per year?
How tall are the players on the Harlem Globetrotters?
Step-by-step explanation:
HELP
10+(-2)=10-2
Therefore 10-2=8
Answer: 1-27 2-8 3-9 4-32
Step-by-step explanation: